(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the gas and effluent losses and the chemical composition of Brachiaria brizantha cv. Piatã with inclusion of bean residue. The inclusion of 0, 10, 20 and 30% of bean residue in Brachiaria grass silage were evaluated in a completely randomized design with five replicates. The results were submitted to analysis of variance and regression, tested by the Tukey test at 5% probability. An increase (P<0,05) of 4,494 percentage units was observed for each 1% inclusion on dry matter recovery. There was a reduction (P<0,05) of 0,259; 0,72 and 0,722 percentage units for each 1% of bean residue on the pH values, losses by gases and effluent, respectively. An increase (P<0,05) of 0,093 was observed; 0,046; 0,191 and 0,031 percentage units for each 1% of the residue added on dry matter, mineral matter, crude protein and ether extract. There was a reduction (P<0,05) of 0,046; 0,233; 0,136 and 0,091 percentage units for each 1% of residue added on organic matter, neutral detergent fiber, acid detergent fiber and hemicellulose.The inclusion of 10% of bean residue in the piatã silage is enough to reduce gas and effluent losses, increase dry matter recovery and improve the chemical composition of the silage.